UNIVERSALITAS DALAM KARYA SASTRA: ASPEK REPRESENTASIONAL, DISKURSIF, DAN NILAI FILSAFAT NOVEL THE ALCHEMIST KARYA PAULO COELHO - Basir, Udjang Pr. M. (ATAVISME, 2008)
"The Alchemist" composition of Paulo Coelho is a novel of world class (winner nobel) that is translated from Spain (0 Alquimista) to various languages, including English and Indonesian. The translation of Indonesian, carried out by Tanti Lesmana (publisher Gramedia), has been considered good enough and used as items of lecturing of art in various college. Its content is wide enough. Besides depicting real fact live with creative touch of his author, it is loaded with various social messages which are so meaningful. At least, there are three important aspects drawn uppermostly in the novel: aspect of representational, diskursif, and philosophy. The author presents various facts of life and historical-geographical reality (aspect representational). For movement of especial figure and develop; build story so that draw used by various strategy, for example occult signal, third person help, and the symbolism (aspect diskursif). And most important is presenting of various human drama which can be taken by its benefit of both for positive and or the negativity (philosophy aspect).